Union Wage, Hours, and Earnings Differentials in the Construction Industry - Perloff, Jeffrey M.; Sickles, Robin C. (Journal of Labor Economics, 1987)
Full-information maximum likelihood is used to estimate union wage, hours, and earnings markups. Construction union wage markups are positive (58.2% at the sample means). Since union hours markups are negative (-4.0%) for most demographic groups, union earnings markups (51.1%) are smaller than the wage markups. All exogenous variables are allowed to interact with the endogenous union dummy variable, which allows us to test whether markups vary across demographic groups, whether increased local unionization has a positive spillover effect in the nonunion sector, and whether increased local unemployment equally affects wages and hours in increased local unemployment equally affects wages and hours in the two sectors.